Misleading silence - Bant, Elise; Paterson, Jeannie Marie (Oxford, UK ; Hart Publishing, an imprint of Bloomsbury Publishing, 2020)
"This collection brings together a team of outstanding scholars from across the common law to explore the treatment of misleading silence in private law doctrine and theory, embracing a comparative analysis. Whereas previous studies have been contractual in focus, here the topic is explored from across the full spectrum of private law. Its approach encompasses equitable, common law and statutory principles and draws on theoretical, historical, cross-disciplinary and doctrinal perspectives. This is truly a landmark publication in private law, with no equivalent in the common law world. Contributors: Professor Rick Bigwood; Professor Michael Bryan; Professor John Cartwright; Professor Mindy Chen-Wishart; Professor Simone Degeling; Professor Pamela Hanrahan; Professor Luke Harding; Professor Matthew Harding; Professor Catharine MacMillan; Professor Hector MacQueen; Professor Donna Nagy; Justice Andrew Phang; Professor Pauline Ridge; Professor Andrew Robertson; Ms Anna Williams"--
Silence and the regulation of misleading conduct : a taxonomy / Elise Bant and Jeannie Marie Paterson -- Critical pressure points in the regulation of silence in misleading conduct / Justice Andrew Phang -- Misleading silence under the Australian consumer law : perspectives from linguistics / Luke Harding and Matthew Harding -- Historical and theoretical perspectives on silence and deception in private law / Michael Bryan -- The norm against misleading conduct and implications for the regulation of 'misleading silence' / Rick Bigwood -- Good faith, cooperation and a reasonable expectation of disclosure in contract performance / Jeannie Marie Paterson -- Affirmative duties in vitiated consent transactions / Mindy Chen-Wishart and Anna Williams -- Affirmative duties in vitiated consent transactions / Mindy Chen-Wishart and Anna Williams -- Misleading silence and unjust enrichment / Elise Bant -- Misleading silence and deceit / John Cartwright -- Misleading silence in mistake / Catharine MacMillan -- Estoppels by silence / Andrew Robertson -- Silent accessories / Pauline Ridge -- Core issues in the regulation of misleading silence in corporate law / Pamela Hanrahan -- Misleading silence as the basis for insider trading liability under the US federal securities laws / Donna Nagy -- Informed consent and declining to opt out of Australian federal class actions / Simone Degeling.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Silence (Law); Consent (Law); Deception; Private international law & conflict of laws; Electronic books